2013
DOI: 10.1111/nmo.12128
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of abdominal distension in severe intestinal dysmotility: abdomino‐thoracic response to gut retention

Abstract: Abdominal distension in patients with severe intestinal dysfunction is related to marked pooling of gut contents, particularly in the small bowel. This increase in content is accommodated within the abdominal cavity by a global and coordinated abdomino-phreno-thoracic response, involving an accommodative ascent of the diaphragm and a compensatory expansion of the chest wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 12 publications
1
20
0
1
Order By: Relevance
“…The program was originally validated in vivo by measuring intestinal gas before and after injection of known volumes of air within the gut . Gas volumes measured in different studies were similar and no trend over time was observed . Using a three‐dimensional reconstruction program with 360° rotation over the three dimensions, gas volumes in selected regions of the gut were also measured.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The program was originally validated in vivo by measuring intestinal gas before and after injection of known volumes of air within the gut . Gas volumes measured in different studies were similar and no trend over time was observed . Using a three‐dimensional reconstruction program with 360° rotation over the three dimensions, gas volumes in selected regions of the gut were also measured.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental human studies have shown that, in response to jejunal gas infusion, patients with abdominal bloating develop gas retention and symptoms, whereas healthy subjects tolerate and rapidly expel the infused gas loads . In apparent conflict with these earlier observations, when such patients complaining of abdominal distension were specifically investigated, only minor abnormalities in intraluminal gas volume and/or distribution were detected either during basal conditions or during symptomatic episodes with abdominal distension . However, due to the limited sample size of healthy subjects and patients included in previous individual studies, undetected abnormalities related to a type II error could not be excluded.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Colonic content and motility are relevant factors when investigating treatments of a number of disorders, such as constipation and irritable bowel syndrome . Knowledge of the distribution of intestinal gas content throughout the gastrointestinal (GI) tract has helped to understand the cause of abdominal symptoms such as bloating and abdominal distension …”
mentioning
confidence: 99%
“…The abdominal wall actively adapts to its content by a tight regulation of its muscular activity . Considering these two elements, ie wall and content, abdominal distension in patients may be related to either an increase in abdominal content, eg intestinal gas accumulation, or to a dyssynergia of the abdominal walls and redistribution of normal content; the latter is a conditioned response that can be corrected by behavioral treatment …”
Section: Introductionmentioning
confidence: 99%